How and why should we regulate the metaverse? - M. S. Sitnikov (Цифровое право, 2025)
The necessity for legal research into the metaverse phenomenon arises due to its considerable economic strength and social capacity. Built on scientific principles and current experience in the metaverse development, this article aims to determine the general outlook for the evolution of legal regulation in the metaverse. The research methodology is based on general methods of scientific knowledge, including analysis, synthesis, systems approach, modeling, and abstraction. The study also employed the following specific scientific methods of legal cognition of reality: formal-legal, historical-legal, comparative, and logical-legal. The distinctive feature of the research consists in its interdisciplinary connection with another branch of knowledge, i.e., political science. As a result, it is shown that the metaverse subject has particularly interested the state, as well as business not only due to the ample opportunities for exploiting the relevant technologies in various areas of life (using public services, educational environment, and others), but also because uncontrolled development of the metaverse can negatively affect public security. The experience of the People’s Republic of China and South Korea holds a special place here. The results of the study enabled the author to identify three possible models of metaverse regulation depending on the level of state control. They are as follows: liberal free (development of the economic component of the metaverse is prioritized), conservative safe (the metaverse sector development should be totally controlled by the state), and mixed (it combines certain key elements of the first two models)..